Perfil sorológico dos doadores de sangue do hemonúcleo de uma região de tríplice fronteira da América do Sul - Oliveira, Vanessa Ruivo de (2024)
Introduction: Blood donation is a simple and easy act. With just one donation, you can help several lives. Unfortunately, this act also has its risks, especially related to diseases transmitted by blood, including sexually transmitted infections. Serological assessment in blood donors is important, especially in international border regions, where people travel from different parts of the world. Objective: To identify the reagent seroprevalence and sociodemographic characteristics in blood donors from the Hemonúcleo of a triple international border city (Foz do Iguaçu-PR, Brazil), referring to the period from January to December 2022. Materials and methods: This is a descriptive, exploratory, documentary research with a quantitative approach. The information was obtained through the analysis of computerized data from the Hemonúcleo Blood Bank System. The data were obtained from February to April 2023. We used the Chi-square test and G test to verify the association between the dependent and independent variables. The analysis were performed using the software Minitad v.18, with statistical significance of p≤0.05. Results: Of the 16,372 candidates, 14,192 donated blood and 471 were unfit due to reactive serology. Thus, the analysis demonstrated that in that period 3.3% of serologies in blood donors from the Hemonúcleo were reactive for some infectious agent. The majority were male (p=0.3792) aged over 29 years (p=0.0001), representing 51.6% and 81.3%. Tests for Hepatitis B were the most prevalent (54.2%), followed by syphilis (34.0%), HIV (3.9%), hepatitis C (3.8%), HTLV (2.1%) and Chagas disease (2.0%), with a predominance of connection or replacement donors. Conclusion: The reagent seroprevalence detected, although similar to the national average, is higher than that found in different national and international regions, indicating that it is a reflection of the phenomena existing in the triple border region, with subsequent favoritism for exposure to behavioral risks. These results may contribute to the development and implementation of new strategies that include the prevention of sexually transmitted infections, with consequent changes in the behavior of the population in the triple border region.